ENVIRONMENTAL SITUATION IN UZBEKISTAN: CHALLENGES AND PROSPECTS - Dilnoza Toymbayeva (Western European Studies, 2024)
Uzbekistan, rich in ancient cities and unique culture, faces serious environmental problems. Situated in the arid region of Central Asia, the country suffers from acute water shortages, soil and air pollution, and land degradation
Keywords: ecology of Uzbekistan; water shortages; pollution